Tolerance in superstructures formed from high-quality colloidal ZnO nanoparticles with hexagonal cross-section. Issue 34 (5th August 2019) - Theiss, Sebastian; Voggel, Michael; Schlötter, Moritz; Sutter, Sebastian; Stöckl, Martin Thomas; Polarz, Sebastian
Abstract : The order of periodic arrays of hexagonal ZnO nanoplates has been investigated in terms of polydispersity. A continuous transition from a crystalline to a glassy state has been found. Abstract : Particle-based materials are expected to exhibit cooperative effects, if nanoparticles form periodic arrays. For particle shapes deviating from a spherical morphology, it is difficult to obtain monodisperse samples. Therefore, we investigated the influence of polydispersity of anisotropic nanoparticles in 2D colloidal crystallization. We work with hexagonal ZnO nanoplates with sizes below 50 nm, and tuned the directionality of the inter-particle interaction by choice of capping agents. Surprisingly, there was no glass to crystal transition for a critical polydispersity value, but a continuous transition.